A micro-Raman study of exfoliated few-layered n-type Bi2 Te2.7Se0.3. Issue 1 (December 2017) - Liu, Fengjiao; Hu, Longyu; Karakaya, Mehmet; Puneet, Pooja; Rao, Rahul; Podila, Ramakrishna; Bhattacharya, Sriparna; Rao, Apparao
Abstract Previously we showed that the thermoelectric (TE) performance of bulkn -type Bi2 Te2.7 Se0.3 can be enhanced by subjecting it to a combined process of chemical or mechanical exfoliation (C/ME) followed by a rapid densification and restacking of the exfoliated layers via the spark-plasma-sintering technique (SPS). Here, we present a systematic micro-Raman study of two-dimensional flakes ofn -type Bi2 Te2.7 Se0.3 produced by the C/ME process, as a function of the flake thickness. We found Raman evidence for flakes with: (i) integer number of quintuples which exhibited a strong electron-phonon coupling, and (ii) non-integer number of quintuples, or sub-quintuples which exhibited the forbidden IR active mode due to symmetry lowering. Detailed atomic force microscopy was used to confirm the number of quintuples in all flakes examined in this study. The restacking and densification of these flakes by SPS promoted the formation of charged grain boundaries, which led to the enhanced TE properties via the energy filtering process.